Constitutive GITR Activation Reduces Atherosclerosis by Promoting Regulatory CD4+ T-Cell Responses—Brief Report. Issue 9 (September 2016) - Meiler, Svenja; Smeets, Esther; Winkels, Holger; Shami, Annelie; Pascutti, Maria Fernanda; Nolte, Martijn A.; Beckers, Linda; Weber, Christian; Gerdes, Norbert; Lutgens, Esther
Abstract : Objective—: Glucocorticoid-induced tumor necrosis factor receptor family-related protein (GITR) is expressed on CD4 + effector memory T cells and regulatory T cells; however, its role on these functionally opposing cell types in atherosclerosis is not fully understood. Approach and Results—: Low-density lipoprotein receptor–deficient mice ( Ldlr −/− ) were lethally irradiated and reconstituted with either bone marrow from B-cell–restricted Gitrl transgenic mice or from wild-type controls and fed a high-cholesterol diet for 11 weeks. Chimeric Ldlr −/− Gitrl tg mice showed a profound increase in both CD4 + effector memory T cells and regulatory T cells in secondary lymphoid organs. Additionally, the number of regulatory T cells was significantly enhanced in the thymus and aorta of these mice along with increased Gitrl and Il-2 transcript levels. Atherosclerotic lesions of Ldlr −/− Gitrl tg chimeras contained more total CD3 + T cells as well as Foxp3 + regulatory T cells overall, leading to significantly less severe atherosclerosis. Conclusions—: These data indicate that continuous GITR stimulation through B cell Gitrl acts protective in a mouse model of atherosclerosis by regulating the balance between regulatory and effector memory CD4 + T cells. Abstract : Supplemental Digital Content is available in the text.